A Comment on the Economics of Labor Adjustment: Mind the Gap: Reply - Caballero, Ricardo J; Engel, Eduardo M. R. A (American Economic Review, 2004)
A Comment on the Economics of Labor Adjustment: Mind the Gap: Reply by Ricardo J. Caballero and Eduardo M.R.A. Engel. Published in volume 94, issue 4, pages 1238-1244 of American Economic Review, September 2004